Differential photoregulation of the nuclear and cytoplasmic CRY1 in Arabidopsis. Issue 4 (22nd February 2022) - Liu, Siyuan; Zhang, Li; Gao, Lin; Chen, Ziyin; Bie, Yaxue; Zhao, Qiannan; Zhang, Shanshan; Hu, Xiaohua; Liu, Qing; Wang, Xu; Wang, Qin
Summary: Arabidopsis cryptochrome 1 (CRY1) is a blue light receptor distributed in the nucleus and cytoplasm. The nuclear CRY1, but not cytoplasmic CRY1, mediates blue light inhibition of hypocotyl elongation. However, the photobiochemical mechanisms distinguishing the CRY1 protein in the two subcellular compartments remains unclear. Here we show that the nuclear CRY1, but not the cytoplasmic CRY1, is regulated by phosphorylation, polyubiquitination and 26S proteasome‐dependent proteolysis in response to blue light. The blue light‐dependent CRY1 degradation is observed only under high fluences of blue light. The nuclear specificity and high fluence dependency of CRY1 explain why this photochemical regulatory mechanism of CRY1 was not observed previously and it further supports the hypothesis that CRY1 is a high light receptor regulating photomorphogenesis. We further show that the nuclear CRY1, but not cytoplasmic CRY1, undergoes blue light‐dependent phosphorylation by photoregulatory protein kinase 1 (PPK1) followed by polyubiquitination by the E3 ubiquitin ligase Cul4 COP1/SPAs, resulting in the blue light‐dependent proteolysis. Both phosphorylation and ubiquitination of nuclear CRY1 are inhibited by blue‐light inhibitor of cryptochromes 1 (BIC1), demonstrating the involvement of photo‐oligomerization of the nuclear CRY1. These finding reveals a photochemical mechanism that differentially regulates the physiological activity of the CRY1 photoreceptor in distinct subcellular compartments. Abstract : See also the Commentary on this article by Batschauer, 234 : 1109–1111 .